1995
DOI: 10.1172/jci118360
|View full text |Cite
|
Sign up to set email alerts
|

Temporal correlation between maximum tetanic force and cell death in postischemic rat skeletal muscle.

Abstract: To gain insight into the mechanisms responsible for muscle dysfunction after ischemia-reperfusion, a rat spinotrapezius muscle preparation was developed which enabled sequential measurements of in vivo maximum tetanic force production and cell death assessed using digital microfluorographic determination of propidium iodide (PI) staining. After 60 min of no-flow ischemia, maximum tetanic force fell significantly during 90 min of reperfusion compared with control, nonischemic muscles. The most striking fall was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…The time course of [Ca 2ϩ ]i change was observed after each of 10 discrete sets of ISO muscle stimulation, in a similar fashion to that described previously (46). Specifically, each set consisted of the muscle being stimulated tetanically at resting spinotrapezius sarcomere length (100 Hz, 5-8 V, stimulus duration 700 ms, 2.6-to 2.8-m sarcomere length) every 3 s for 2.5 min (i.e., 50 contractions).…”
Section: Groupmentioning
confidence: 79%
See 1 more Smart Citation
“…The time course of [Ca 2ϩ ]i change was observed after each of 10 discrete sets of ISO muscle stimulation, in a similar fashion to that described previously (46). Specifically, each set consisted of the muscle being stimulated tetanically at resting spinotrapezius sarcomere length (100 Hz, 5-8 V, stimulus duration 700 ms, 2.6-to 2.8-m sarcomere length) every 3 s for 2.5 min (i.e., 50 contractions).…”
Section: Groupmentioning
confidence: 79%
“…For example, Ivanics and colleagues (23) have described a selective damage (and [Ca 2ϩ ] i accumulation) in oxidative type I fibers following an ischemia-reperfusion protocol in the spinotrapezius muscle. In contrast, Suzuki and colleagues (46) found that an ischemiareperfusion protocol selectively damaged those fibers with a low oxidative capacity (most likely type IIb fibers, as visualized using rhodamine-123 to identify relative mitochondrial content). When muscle is injured consequent to ECC contractions, muscle fibers may be selectively damaged, and, as these fibers subsequently produce less force, the remaining healthy fibers may be subjected to greater stresses and are likely to suffer progressively more injury (14).…”
Section: Ca 2ϩ Propagation In Muscle Fibersmentioning
confidence: 92%
“…Unfortunately, there are very few muscles anatomically and optically suitable for transmission light microscopy. Of these, the rat spinotrapezius muscle possesses the following singular advantages: 1) it can be exteriorized and transilluminated without disruption of the nervous or primary vascular supplies (2,12,28,40); 2) it comprises a mosaic of the three principal fiber types found in mammalian muscle (8); and 3) the oxidative capacity approximates that found in the untrained human quadriceps (8,22). Consequently, it is not surprising that intravital microscopy of the spinotrapezius has been integral to our understanding of muscle microcirculation in health (4,21,23,25,31,37,39) and chronic diseases such as heart failure (15), Type 1 diabetes (18), and hypertension (13).…”
mentioning
confidence: 99%
“…Furthermore, leukocyte adherence to the venular endothelium occurs predominantly during reperfusion rather than during ischemia (4,7,8,22,23), whereas in hypoxia this phenomenon occurs when PO 2 is reduced (19,20,24); during normoxic recovery, leukocyte-endothelial adhesive interactions actually subside (19,20,24). Systemic hypoxia in anesthetized rats, however, results in marked arterial hypotension (26).…”
mentioning
confidence: 99%